PENYULUHAN DAN SKRINING JAMUR KUKU PADA PETUGAS SAMPAH - Fahmi, Norma Farizah (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2024)
Onychomycosis is a fungus infection of the nail plate caused by dermatophytes, non dermatophytes and yeast . The factor that causes nails to become infected with fungus is frequent direct contact with a damp and dirty environment. The purpose of this study is to determine the presence of fungal infections Trichophyton sp., Aspergillus sp. and Candida albicans on the nails of garbage officers at the Bangkalan District Environmental Service. The research method used was descriptive and the research design was cross sectional. The variable in this study was the nail fungus of the garbage man. The samples used were 46 samples from a total population of 91 respondent. This research was conducted at the Microbiology Laboratory of STIKes Ngudia Husada Madura. The results obtained from this study with a total sample of 46 showed nails infected with the fungus Trichophyton sp., totaling 3 samples with a percentage of 9%, Aspergillus sp. as many as 10 samples with a percentage of 29% and Candida albicans 0%. Factors that caused nails to become infected with fungus are frequent contact with a damp and dirty environment, not washing hands and feet with soap, often not using footwear and not using personal protective equipment when working. The results of this study contained the fungus Trichophyton sp. and Aspergillus sp. on the nails of the garbage officer at the Bangkalan District Environmental Service. Prevention of nail infections in garbage officers can be done by using personal protective equipment (PPE) at work, washing hands and feet with soap and keeping nails clean.